2012
DOI: 10.15218/zjms.2012.0011
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in women with breast cancer in Erbil city: a case-control study

Abstract: Background and objectives: Breast cancer has specific challenges for women. This study was carried out to identify the frequency of depression and anxiety in women with breast cancer.. Methods:A hospital based case-control study was carried out in Erbil city from August, 15 th to November, 1 st 2010. The convenient sample included 100 cases of diagnosed breast cancer for the last three years attending Maternity and Nanakali hospitals and two hundred age-matched (± 5 years) non-cancer women attending the Matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus, scores on each subscale range from 0 to 21. High scores indicate relatively severe symptoms; the severity of symptoms is interpreted as normal (0-7), borderline abnormal (borderline case) (8-10), abnormal anxiety (case) (11)(12)(13)(14), and high [25].…”
Section: Part Iii: the Hospital Anxiety And Depression Scale (Hads)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, scores on each subscale range from 0 to 21. High scores indicate relatively severe symptoms; the severity of symptoms is interpreted as normal (0-7), borderline abnormal (borderline case) (8-10), abnormal anxiety (case) (11)(12)(13)(14), and high [25].…”
Section: Part Iii: the Hospital Anxiety And Depression Scale (Hads)mentioning
confidence: 99%
“…A study done in Erbil city revealed that increased levels of anxiety and depression after a diagnosis of BC highlight the need for dedicated psychiatric service provision. Psychological interventions for women with BC should involve an account of the broader social context in which cancer occurs, with a focus on improving social support [14].…”
Section: Introductionmentioning
confidence: 99%
“…One large cohort study found pure anxiety symptoms in 14.7% [7]. According to the study done by Kameran et al (2012) in Erbil city -Iraq, increased levels of melancholy and anxiety following a breast cancer diagnosis underscore the need for specialized psychiatric services [8].Breast cancer risk factors include both social and biological aspects including women's age, menarche at a young age, delayed first birth and menopause, nulliparity, short-term lactation, birth control pills, obesity, excessive fat consumption, hormone replacements Moreover, several epidemiological and clinical investigations have identified women with a family history of breast cancer as significant risk factors for the disease. On the other hand, the majority of breast cancer intervention literature suggests that modifiable risk factors can be avoided by promoting a healthy diet, regular physical activity, regulating alcohol consumption, and controlling weight, all of which are likely to reduce breast cancer incidence over time [9].…”
mentioning
confidence: 99%